Performance of Malaysia REIT Stocks Relative to Bursa Malaysia Stock Index - Hui, Tan Shiao (2009)
The purpose of this research aims to investigate the performance of Malaysia REIT s stock relative to Bursa Malaysia stock index over the period from June 2007 to June 2009.